Adaptation and patterns of its effects on the continuity of a healthy way of life of senior pupil and first-year students - Vovk V.M; Priymak A.Yu (Kharkov National Pedagogical University, 2013)
Reviewed and analyzed the literature on adaptation of youth. The results of the monitoring of the impact of factors on the process of adapting a healthy lifestyle succession of senior and first-year students. The experiment involved 298 high school students and 296 first-year students. It is established that the category of "adaptation" is the most important educational component of a healthy lifestyle. This category is effectively influence the process of succession healthy living and active sports activity pupils and students. The strategic goal of secondary and higher education should be to create an environment that promotes the physical and moral improvement of young people, promoting a healthy lifestyle. It is proved that adjustment disorder is expressed in the deterioration of health, physical development, bio-energy physical activity of young people.